Laparoscopic management of interstitial pregnancy with automatic stapler. (23rd October 2012) - Ahsan Akhtar, Muhammad; Izzat, Feras; Keay, Stephen D
Abstract : A 36-year-old woman was referred by general practitioner to the early pregnancy unit with pelvic pain in her seventh week of pregnancy. She had a transvaginal ultrasound. Unruptured live twin tubal ectopic pregnancy was diagnosed on. Diagnostic laparoscopy revealed an unruptured left interstitial ectopic pregnancy. The interstitial tubal pregnancy was removed by laparoscopic automatic stapler with minimal blood loss. The patient had an uneventful recovery to health.